Pola Komunikasi Keluarga dalam Mendidik Anak Usia Dini - Khermarinah Khermarinah (Insititut Agama Islam Negeri (IAIN) Curup, 2021)
Basically, humans created by God are given with two roles at once, namely being personal beings and social beings. When performing both roles, humans need a method called communication. The purpose of this study is to examine the implementation of family communication patterns in educating early childhood. Method in this study uses descriptive qualitative, namely tracing the pattern of family communication in educating early childhood. Based on the results of the study, it also explained that there was a willingness to understand and family sensitivity about the urgency of family communication and includes controlling the temperament of children at an early age which is still low. It was judged that the family was often concerned with the context of the relationship between the two things. The conclusion is that in fact in the family they use to communicate to educate children, especially early childhood, they do not pay attention to the child's absorption of the message conveyed by the family. Families in communicating to educate early childhood are only in the form of orders, orders and reprimands, and very few families are directly involved in educating early childhood. Where the involvement of parents, positive habits of parents do not occur in the communication.